2008
DOI: 10.1007/s10571-007-9254-x
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Level in the Rat Prefrontal Cortex Increases Following Chronic but Not Acute Treatment with Duloxetine, a Dual Acting Inhibitor of Noradrenaline and Serotonin Re-uptake

Abstract: Our results show a major finding that repeated, but not single, Duloxetine treatment increases the level of BDNF in the prefrontal cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 78 publications
10
31
0
Order By: Relevance
“…The mature form and the precursor form of BDNF play different roles in cell survival, synaptic plasticity and cognitive functions in health and pathology [46] . In animals, we recently showed that the mature, but not the precursor form of BDNF was significantly increased in the prefrontal cortex of rats treated for 14 days with duloxetine at 30 mg/kg/day [47] .…”
Section: Discussionmentioning
confidence: 99%
“…The mature form and the precursor form of BDNF play different roles in cell survival, synaptic plasticity and cognitive functions in health and pathology [46] . In animals, we recently showed that the mature, but not the precursor form of BDNF was significantly increased in the prefrontal cortex of rats treated for 14 days with duloxetine at 30 mg/kg/day [47] .…”
Section: Discussionmentioning
confidence: 99%
“…[34,[90][91][92][93] Given that a failure in the central NE regulation of HPA activity and the subsequent inability to regulate the stress response can contribute to the pathogenesis of mood and anxiety symptoms, the neuroplastic changes after antidepressant treatments suggest that NE and/or 5-HT can have a direct role in regulating BDNF expression, and a disruption of NE and/or 5-HT functions in the brain can contribute to the cellular mechanisms underlying anxiety and depression. [34,[91][92][93][94][95][96][97] Furthermore, nonpharmacological approaches (e.g., exercise, diet control, and life-style changes) also increase BDNF and neurogenesis. [78,[98][99][100] These approaches may constitute an indirect way to modulate NE functions, which, in turn, regulate BDNF and neurogenesis-dependent mechanisms to normalize the state of anxious depression.…”
Section: Stress Ne Brain-derived Neurotrophic Factor and Adult Neurmentioning
confidence: 99%
“…The effect on NA and 5-HT uptake resulting from the acute and chronic administration of some drugs depends on the time of administration (Mannari et al, 2008).…”
Section: Discussionmentioning
confidence: 99%